Development of Malaysian Mammal Online Database - Mustafa, Intan Rabitah; Omar, Mohd Shahir Shamsir; Mustapha, Aida; Azman, Mohammad Shahfiz (Journal of Sustainable Natural Resources, 2022)
Malaysia is one of 17 mega diverse countries in the world. Despite this fact, there is still no online standalone database that focuses on Malaysian mammals.  Creation of a mammalian database would allow researchers and conservationists to utilize the database for research, policy making and to answer broad scale of biodiversity questions.  Human development have contribute to the depleting of mammal population and species extinction rate is faster than the effort of cataloguing them. The aim of this study is to 1) identify online database features and the type of data required for mammal database, 2) collect and populate database from existing mammal data to assist the said database and 3) to test the acceptance of the database by user of this study. The secondary data from existing database was collected to determine the required features needed in the database. The database adhere to TDWG standard that facilitates exchange of biological information. Rapid Prototype Model was utilized as development method and Omeka Classic was used as platform of Content Management System. The mammal data was collected online and populate into the database. The acceptance testing in form of questionnaire were distributed to verify whether the database is function properly and meet the requirement of the study. We present MYMODS, a comprehensive mammal database with 361 mammal species in Malaysia deposited in the database. The development of this database will enable the researcher and conservationist to seek and identify mammal information based on speciesâ€™ scientific name, description and IUCN Red List. We believe that MYMODS will contribute to the digital knowledge that provide tools for mammal research and contributes in management of biodiversity and conservation in Malaysia. MYMODS is available at https://cercom.uthm.edu.my/mymods/